Cultivating Harmony: Strengthening Religious Inclusivity Through Interfaith Dialogue in Rural South Tapanuli - Puji Kurniawan; Liah Rosdiani Nasution; Ahmatnijar (Fakultas Studi Islam dan Peradaban, Universitas Muhammadiyah Yogyakarta, 2025)
Interfaith dialogue in rural contexts remains underexplored, despite the unique dynamics of social and religious coexistence in such areas. This study aims to answer two central research questions: (1) How is interfaith dialogue practiced in a multireligious rural community? and (2) How does such dialogue shape or hinder religious inclusivity? The research was conducted in Tantom Angkola, North Sumatra, a village inhabited by Muslim and Christian communities with a long history of coexistence. Using a qualitative approach, in-depth interviews were conducted with 15 participants from diverse generational, religious, and social backgrounds. Thematic analysis revealed four key themes: (1) Perceptions of Religious Harmony, (2) Barriers to Deeper Interfaith Engagement, (3) Everyday Interactions between Faith Communities, and (4) Aspirations for Future Inclusivity. Findings showed that interfaith dialogue mostly occured informally and through social structures rather than theological exchanges, reflecting superficial tolerance but not yet full inclusivity. Key barriers include religious stereotypes, cultural conservatism, and lack of institutional support. The discussion draws on Swidler’s Decalogue of Interfaith Dialogue and is contextualized within Islamic pedagogical traditions such as halaqah (study circles) and the ethical principle of wasathiyah (moderation). The study concluded that revitalizing Islamic principles of justice for minorities and fostering locally grounded interfaith education are essential for advancing deeper inclusivity in rural contexts.